2017
DOI: 10.1186/s12867-017-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

Splicing arrays reveal novel RBM10 targets, including SMN2 pre-mRNA

Abstract: BackgroundRBM10 is an RNA binding protein involved in message stabilization and alternative splicing regulation. The objective of the research described herein was to identify novel targets of RBM10-regulated splicing. To accomplish this, we downregulated RBM10 in human cell lines, using small interfering RNAs, then monitored alternative splicing, using a reverse transcription-PCR screening platform.ResultsRBM10 knockdown (KD) provoked alterations in splicing events in 10–20% of the pre-mRNAs, most of which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
(69 reference statements)
0
24
0
Order By: Relevance
“…Inactivating mutations appear to span the entire grade/stage spectrum of NMIBC ( Table 1). Knockdown of RBM10 leads to altered splicing of a wide range of genes in cancer cell lines, several of which are associated with RAS signaling [50].…”
Section: Mutated Genesmentioning
confidence: 99%
“…Inactivating mutations appear to span the entire grade/stage spectrum of NMIBC ( Table 1). Knockdown of RBM10 leads to altered splicing of a wide range of genes in cancer cell lines, several of which are associated with RAS signaling [50].…”
Section: Mutated Genesmentioning
confidence: 99%
“…RBM10 mutation has particular relevance to TARP syndrome, and may have relevance to spinal muscular atrophy (SMA) . Unfortunately, actual changes in RBM10 expression have not been rigorously examined in either of these diseases.…”
Section: Regulation Of Rbm10mentioning
confidence: 99%
“…Moreover, alteration of mRNA alternative splicing, especially exon skipping ( 7 ) or exon-inclusion of the affected proteins ( 7 , 9 ), results in abnormal protein expression and functions in cells. RBM10 knockdown provoked alterations in 10–20% of the pre-mRNA splicing events ( 10 ), while other studies showed that RBM10 is a tumor suppressor gene ( 11 , 12 ) Thus, RBM10 may play an important role in suppression of human tumorigenesis. Previous studies showed that RBM10 mutations did occur in lung and pancreatic cancers ( 13 , 14 ) and the Cancer Genome Atlas (TCGA) data showed that RBM10 mutations occurred in 8% of lung adenocarcinoma and is more common in male patients.…”
Section: Introductionmentioning
confidence: 99%